PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN DAN KEBIJAKAN UTANG TERHADAP NILAI PERUSAHAAN - Mayogi, Dien Gusti; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The higher the level of prosperity of the owner of the company, it can increase the value of the company. The value of the company is reflected in its share price. The value of the company shows that the prosperity of shareholders high and the future prospects of the company in good shape. The companys value in this study is proxied by Price Book Value (PBV). This research is meant to find out how great the influence of profitability, dividend policy and debt policy to the firm value. This research has been done by using the analysis test of SPSS. The samples are companies which are listed in manufacturing sector in Indonesia Stock Exchange from 2011 to 2013. 12 companies which have met with the sample collection criteria have been obtained so the numbers of observations in this research are 36 observations. This research has been done by using multiple regression analysis in order to see the influence of independent variables on the dependent variable either partial or simultaneous. The result of this research shows that profitability variable has an positive influence to the firm value. Dividend policy has an positive influence to the firm value whereas debt policy does not have any influence to the firm value.Keywords: Profitability, Dividend Policy, Debt Policy, Firm Value.